(untitled) (Colloquia Comparativa Litterarum, 2025)
The aim of this study is to present the modern interpretations of the first Biblical couple in the interwar European novel. Works from French, Romanian and Bulgarian literature have been taken as examples on whose basis analysis has been made of the possible convergence of ideas in Europe during that period. The figure of the first Biblical family has been attracting writers in their aesthetic quests through the reflection on social models and the fulfillment of Man and Woman. Considering this context, the refusal of posterity becomes a painful theme. There is a dilemma between the desire to preserve the couple in the initial stage of innocence before the Fall and the intent to end the cycle of errors repeated by mankind. Last but not least, the theme raises the question of the newly emerging female identity which breaks away from the traditional roles of mother and wife.